Microbial gradual shifts during the process of species replacement in Taihang Mountain - Liu, Xiuping; Zhou, Wangming; Wang, Xinzhen; Wu, Hongliang; Dong, Wenxu (Frontiers in Microbiology, 2023)
Understanding microbial gradual shifts along species replacement can help elucidate the mechanisms driving secondary succession, and predict microbial responses to changing environments. However, how climate-induced species replacement alters microbial processes, and whether microbial shifts follow predictable assembly trajectories remain unclear. Using space-for-time substitution approach, we studied shifts in bacterial and fungal communities in the succession from Leptodermis oblonga to Vitex negundo var. heterophylla shrubland in Taihang Mountain. Species replacement, induced by climate related environmental change, significantly increased the above-ground biomass of shrublands, and TP and TK contents in topsoil. The succession from L. oblonga to V. negundo var. heterophylla communities resulted in the gradually replacement of cold-tolerant microbes with warm-affinity ones, and alterations of microbial communities involved in soil biogeochemical processes. Soil and plant variables, such as above-ground biomass, soil pH, total phosphorus, and total potassium, well explained the variations in microbial communities, indicating that the coordinated changes in plant communities and soil properties during secondary succession caused accompanied shifts in microbial diversity and composition.